APPLICATION OF THE COCHRANE-ORCUTT METHOD IN ANALYZING THE IMPACT OF WATER QUALITY DYNAMICS ON THE GROWTH OF VANNAMEI SHRIMP (Litopenaeus vannamei) - Febriyani Eka Supriatin; Aulia Rahmawati (Jurnal Statistika Universitas Muhammadiyah Semarang, 2024)
Vannamei shrimp (Litopenaeus vannamei) is a key commodity in aquaculture due to its high survival rate, short cultivation period, and disease resistance. Water quality plays a crucial role in shrimp growth and productivity, particularly in intensive farming systems. This study aims to analyze the effects of water quality dynamics (pH, temperature, and dissolved oxygen) on shrimp growth, measured through Average Body Weight (ABW) and Specific Growth Rate (SGR). Multiple linear regression analysis was employed, but given the time-series nature of water quality data, the assumption of non-autocorrelation was violated. To address this issue, the Cochrane-Orcutt method was applied to obtain efficient parameter estimates and valid hypothesis testing results.The findings indicate that temperature significantly affects ABW and SGR (p < 0.05), while pH and dissolved oxygen do not show a significant partial effect. The simultaneous F-test confirms that these three water quality variables collectively influence shrimp growth. The Durbin-Watson test revealed autocorrelation in the initial model, which was resolved through the Cochrane-Orcutt method. The final regression model demonstrated improved estimation accuracy without autocorrelation. This study highlights that temperature is the primary factor influencing vannamei shrimp growth, while pH and dissolved oxygen play supporting roles in maintaining an optimal environment. Furthermore, the Cochrane-Orcutt method proved effective in addressing autocorrelation, ensuring more accurate analysis results that can guide the management of intensive vannamei shrimp farming